ESRA19-0515 Efficacy of transmuscular quadratus lumborum (QL-3) block for analgesia after total hip arthroplasty: a randomized controlled trial. (30th August 2019) - Manuwong, S; Curry, P; Plukmonton, C; Lerdpaitoonpan, W
Abstract : Background and aims: Total hip arthroplasty (THA) is associated with significant postoperative pain. the transmuscular quadratus lumborum block (TQLB) has been described to be effective in postoperative pain relief after THA, but no randomized, controlled study has been reported. To study the efficacy of the ultrasound-guided (USG) TQLB in post-operative pain control after THA. Methods: In this prospective, randomized controlled study, we enrolled 40 patients ASA class I to III and scheduled for elective THA. They were randomly assigned into two groups: TQLB group (TQL-gr) and control group (C-gr). the patients in TQL-gr received an USG TQLB with 0.25% bupivacaine followed by spinal anesthesia and the patients in C-gr received spinal anesthesia only. All patients received a patient-controlled IV morphine. the primary outcome was morphine consumption during the first 24 hours postoperatively. Secondary outcomes were pain score at rest and on movement after the surgery. the time to first step, adverse effects and patient satisfaction were also recorded. Results: 40 patients completed the study, 20 in each group. the accumulative morphine consumption in 24 hours after the surgery were comparable in both groups (13.85±10.31 vs 16±11.77, p>0.05). the morphine consumption at 2, 6, and 12 hours was also similar. the post-operative pain scores at 2, 6, 12 and 24 hours were not different. the time to first step were 20.75±3.61 in TQLB-gr and 21.25±4.63 in C-gr (p>0.05). the adverse effects and patient satisfaction were comparable. Conclusions: The USG TQLB with 0.25% bupivacaine does not reduce postoperative pain and morphine consumption during the first 24 hours after THA.